GUIDELINES FOR THE LEADER AND THE COMMANDER - Clarke, Bruce C. (Bruce Cooper), 1901-1988 (Stackpole Books, 1973)
"Guidelines for the Leader and the Commander is an enduring classic. Written by the Army's premier trainer of the twentieth century, this is a wide-ranging collection of principles and maxims to guide the building, training, and leading of any organization, with a focus on the individuals who make up that organization. Clarke intended the book to enlighten and instruct leaders, and those who aspire to leadership, in every profession and every walk of life. Thoughtful as well as concrete, pithy and often conversational, Clarke's book resonates today."--Back cover